Položaj gluhoslepih v Sloveniji - Gerenčer Pegan, Simona (Socialno delo, 2008)
Individuals who are deafblind suffer from simultaneous hearing and visual impairments to an extent which makes them unable to function independently in their everyday lives, despise their use of aids. Deafblindness is a specific form of disability requiring special treatment approach and communication. In the legislation of the European Union, deafblindness is recognised as a specific form of disability; a declaration concerning deafblind persons has been adopted and organisations established which fight for their rights. Slovenia legislation provided for the needas of deaf persons and for the blind ones, but not for the deafblind persons.Although there are indicators that the state has perceived the existence of deafblind individuals, so far nosignificant motions have been made in the field. As long as deafblindness isnot recognised as a special form of disability, people with simultaneous hearing and visual impairments will be unable to obtain the status of deafblind persons, meaning they will be classified either as deaf or blind individuals, and they will only be eligible to benefits provided to either deaf or blind persons. In 2006, the Association of Deafblind Individuals DLAN was founded, raising awareness of the professional and wider public about this problem.
Keywords: gluhoslepi; Slovenia; Slovenija; gluhi; slepi